Comparative study of integrated transceiver for real time monitoring in rescue operation - Uddin, Md. Nasir; Rashid, Muhammad Mahbubur; Nithe, N. A. (2016)
An augmented reality system provides enhanced situational information to personnel located within an environment. A tracking system obtains viewpoint information corresponding to a real-time view of said environment. A processing system receives information from one or more sensors. Information includes sensor location information and status information about the environment and personnel therein. The processing system generates graphics using the sensor location information and the viewpoint information. Graphics include visual representations of said status information. A display displays the generated graphics on a display at a supervisor station that is outside of said environment such that graphics are superimposed on the real-time view.